2021
DOI: 10.33448/rsd-v10i15.21960
|View full text |Cite
|
Sign up to set email alerts
|

Poisoning in Children and adolescents assisted during the COVID-19 pandemic at the Toxicological Information and Assistance Center in Federal District, Brazil (CIATOX -DF): Descriptive, Cross-sectional, and Analytical study with 1.037 patients

Abstract: Exogenous poisonings are one of the principal accidents involving children and adolescents. The social isolation promoted by the COVID-19 pandemic raises concerns about the possibility of an increase in poisoning among children since most cases of poisoning occur in home environments. Therefore, the present study evaluated exogenous poisonings in children under ten years of age and adolescents aged 11 to 20 years old through data recorded at the Toxicological Information and Assistance Center in the Federal Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The second wave of the German Health Interview and Examination Survey for Children and Adolescents (KiGGS Wave 2, 2014-2017) showed that, under the consideration of previous studies [1], unintentional injuries in children remain at a continuously high level, especially in times of changing conditions and associated shifts in risk. For example, at the start of the COVID-19 pandemic, physicians initially predicted a higher risk of unintentional poisoning incidents because of the increased use of cleaning agents and disinfectants [2], which was later reported in studies from several countries (Italy [3], Brazil [4], United States [5], Iran [6], Australia [7], and Morocco [8]). Shifting risks and associated consequences for the well-being of children clearly underline the importance of research and measures to prevent unintentional child injuries.…”
Section: Introductionmentioning
confidence: 97%
“…The second wave of the German Health Interview and Examination Survey for Children and Adolescents (KiGGS Wave 2, 2014-2017) showed that, under the consideration of previous studies [1], unintentional injuries in children remain at a continuously high level, especially in times of changing conditions and associated shifts in risk. For example, at the start of the COVID-19 pandemic, physicians initially predicted a higher risk of unintentional poisoning incidents because of the increased use of cleaning agents and disinfectants [2], which was later reported in studies from several countries (Italy [3], Brazil [4], United States [5], Iran [6], Australia [7], and Morocco [8]). Shifting risks and associated consequences for the well-being of children clearly underline the importance of research and measures to prevent unintentional child injuries.…”
Section: Introductionmentioning
confidence: 97%
“…The second wave of the German Health Interview and Examination Survey for Children and Adolescents (KiGGS Wave 2, 2014-2017) showed that, under the consideration of previous studies [ 1 ], unintentional injuries in children remain at a continuously high level, especially in times of changing conditions and associated shifts in risk. For example, at the start of the COVID-19 pandemic, physicians initially predicted a higher risk of unintentional poisoning incidents because of the increased use of cleaning agents and disinfectants [ 2 ], which was later reported in studies from several countries (Italy [ 3 ], Brazil [ 4 ], United States [ 5 ], Iran [ 6 ], Australia [ 7 ], and Morocco [ 8 ]). Shifting risks and associated consequences for the well-being of children clearly underline the importance of research and measures to prevent unintentional child injuries.…”
Section: Introductionmentioning
confidence: 99%